2010
DOI: 10.1245/s10434-010-1465-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency is Correlated with Poor Outcomes in Patients with Luminal-type Breast Cancer

Abstract: PurposeVitamin D deficiency may be an indicator of poor prognosis in patients with breast cancer before surgery. We investigated the association between serum vitamin D concentration and breast cancer prognosis according to intrinsic cancer subtypes.MethodsFrom June to December 2006, serum 25-OHD was measured in 310 Korean women with breast cancer who were treated at the Asan Medical Center, Korea. Clinicopathologic data were examined to determine the prognostic effects of serum 25-OHD. Expression of estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 27 publications
2
51
2
1
Order By: Relevance
“…Finally, the observation that the patients with HER2-/ HR? tumors were more likely to have vitamin D insufficiency already at baseline might be important given the recent description of the association between vitamin D insufficiency and poor prognosis mainly in luminal-like breast cancers [58].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the observation that the patients with HER2-/ HR? tumors were more likely to have vitamin D insufficiency already at baseline might be important given the recent description of the association between vitamin D insufficiency and poor prognosis mainly in luminal-like breast cancers [58].…”
Section: Discussionmentioning
confidence: 97%
“…Other breast cancer outcomes include distant disease-free survival (16,18,19), disease-free survival (19,21), and relapse (19,20). Circulating 25-OHD concentrations were associated with longer distant disease-free survival (16,18,19).…”
Section: Breast Cancermentioning
confidence: 99%
“…Hence, an in-depth investigation of how tumor characteristics and lifestyle factors modify the associations of vitamin D with prognosis is needed. Only two of the six breast cancer studies reported analyses stratified by stage at diagnosis and hormone receptor status (18,21), one with BMI (18), and none with race. Of particular importance and interest is to determine whether part of the racial and obesityrelated differences in cancer survival can be explained by differences in the 25-OHD levels.…”
Section: The Role Of Tumor Characteristics and Lifestyle Factorsmentioning
confidence: 99%
“…luminal type but they have not explained any mechanism for ER negative cancers. [15] However, In a recent study, it was shown that by upregulating the vitamin d receptors in murine model of TNBC, antiproliferative effect is enhanced [16] and thus explaining the effect of vitamin D in TNBC subtype breast cancer. Further studies explaining the exact molecular mechanism underlying such observations needs to be carried out.…”
Section: Discussionmentioning
confidence: 99%